Calculs ab-initio des propriétés structurales, électroniques et magnétiques des semi-conducteurs et oxydes magnétiques dilués tridimensionnels - EL-ACHARI Tarik (Faculté des Sciences de Rabat, 2021)
The aim of this thesis is to study the structural, electronic and magnetic properties of three-dimensional dilute magnetic semiconductors and oxides using DFT. We started by presenting the field of spintronics and semiconductor materials, then we studied the magnetic phenomena presented in solids. Then, we set out the theoretical methods that will allow the study of materials and solids we distinguish and particularly the density functional theory (DFT) and the KKR method. In the last chapter we present our various contributions in the field of spintronics, starting by examining the possibility of obtaining half-metallicity in Mn and V doped SnC tin carbide. Then study Mn doped CeO2. Then explore the electronic and magnetic properties of (Ti, V, Cr, Mn and Co) -doped CdS. And finally analyze the electronic and magnetic properties of zinc-blende AlN doped
Ab-initio calculations of the structural, electronic and magnetic properties of three-dimensional dilute magnetic semiconductors and oxides
Keywords: DFT; KKR; Spintronique; DMS/DMO; Half; Métaux; Température de Curie; Physique